Seasonal maturation of Glypthelmins vitellinophilum (Trematoda: Digenea) in Lysapsus limellus (Anura: Pseudidae) from an argentinean subtropical permanent pond - Hamann, Mónika Inés (2006)
From December 1995 to November 2000, the seasonal maturation of Glypthelmins vitellinophilum Dobbin, 1958, in its definitive host, the frog Lysapsus limellus Cope, 1862, was studied in a subtropical permanent pond in northeastern Argentina. The objectives of this study were: 1) to determine the infrapopulation dynamics of the parasite, analyzing the seasonal maturation cycle throughout the years; and 2) to examine the relationship between the intensity of trematode infection in different developmental stages (recruitment, growth and maturation) and the host's body length. Of a total of 1,400 frogs examined over 60 months (5 years), 38% were found to be infected with G. vitellinophilum, and the intensity of infection was 1-15 trematodes per frog. Specimens of G. vitellinophilum were present in L. limellus throughout the years, but did not show a pronounced seasonal maturation cycle. Possible reasons for these findings are discussed with reference to climatic fluctuations and biotic factors. The infective period of the parasite (stage I) occurred in summer, autumn and spring, coinciding with the time each frog cohort appeared. These infections were found principally in small body sizes (classes 1 and 2) of L. limellus. Juvenile and nongravid specimens of worms (stage II and III) were found in frogs of different body sizes throughout the period of investigation. Gravid specimens of the parasite (stage IV) were generally recorded in autumn, winter and spring, mainly in the bodies of larger frogs. The body length of Trematodes in stages I and IV was significantly and positively correlated with that of the frogs.